9z+4-5z-5=

Simple and best practice solution for 9z+4-5z-5= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 9z+4-5z-5= equation:


Simplifying
9z + 4 + -5z + -5 = 0

Reorder the terms:
4 + -5 + 9z + -5z = 0

Combine like terms: 4 + -5 = -1
-1 + 9z + -5z = 0

Combine like terms: 9z + -5z = 4z
-1 + 4z = 0

Solving
-1 + 4z = 0

Solving for variable 'z'.

Move all terms containing z to the left, all other terms to the right.

Add '1' to each side of the equation.
-1 + 1 + 4z = 0 + 1

Combine like terms: -1 + 1 = 0
0 + 4z = 0 + 1
4z = 0 + 1

Combine like terms: 0 + 1 = 1
4z = 1

Divide each side by '4'.
z = 0.25

Simplifying
z = 0.25

See similar equations:

| -6(r-7)=-54 | | 8+9a=7 | | 4x+3+2y=11 | | 7x-4.23=0.2+2.57 | | 7x-4.23=0.2 | | -8(n-2)-2=-21-3n | | 3x=2(7x-3) | | 80+5x=7x | | 4(5r-5)=-20-7r | | -5=7-2x | | (3x-1)(x+2)=-1 | | -x-3(-5x-8)=136 | | (12^5)/(9^2)*(4^4) | | 12^5/9^2*4^4 | | 0.3x-2(0.1x+0.4)= | | (3a-9)/(3a-6)*(a/a^2-9) | | {(3a-9)/(3a-6)}*(a/a^2-9) | | f(x)=-3.25(-4.2) | | 18=2v+4 | | 6+2(5x-1)=84 | | 18-12a= | | 108=-6(3+3x) | | 5h-3h+9h= | | 42n-12=0 | | Log(7)25=2log(7) | | 3a-9/3a-6*a/a^2-9 | | 7(4+h)=13h | | sin(2x-60)=-cos(3x) | | 121=-11b | | 5p-7=2p | | 90-x=0.8(x) | | 1/2d-12 |

Equations solver categories